Strengthening Digital and English Skills for Work Readiness in RW 08 Kalideres West Jakarta - Rizky Mirani Desi Pratama; Dwi Puji Hastuti; Cucu Ika Agustyaningrum (STMIK Royal, 2026)
Abstract: This community service program was carried out by Universitas Bina Sarana Informatika (UBSI) with the aim of strengthening digital skills and English proficiency among high school/vocational school graduates in order to improve their job readiness. The activity took place at Balai RW 08, Kalideres, and West Jakarta. This program was motivated by the condition of high school/vocational graduates in RW 08, most of whom come from lower-middle-income families and are therefore more inclined to enter the workforce directly rather than pursue higher education. Thus, training is needed to enhance practical skills relevant to industry requirements.The training focused on three main aspects, developing a professional curriculum vitae (CV), strategies for facing job interviews in both Indonesian and English, and practicing digital skills through the use of Canva for CV creation. Participants were actively engaged through interactive sessions, simulations, and collaborative exercises. The results of the program indicated increased awareness, confidence, and skills among participants in preparing themselves to enter the workforce. The conclusion of this program is that integrating digital literacy and English proficiency in community-based training can enhance the competitiveness of high school/vocational school graduates and make a tangible contribution to supporting their readiness for the job market. Keywords: english proficiency, job readiness, digital skills, community service, vocational education Abstrak: Program pengabdian kepada masyarakat ini dilaksanakan oleh Universitas Bina Sarana Informatika (UBSI) dengan tujuan memperkuat keterampilan digital dan kemampuan berbahasa Inggris lulusan SMA/SMK untuk meningkatkan kesiapan kerja. Kegiatan ini berlangsung di Balai RW 08, Kalideres, Jakarta Barat. Program ini dilatarbelakangi oleh kondisi lulusan SMA/SMK di RW 08 yang sebagian besar berasal dari keluarga ekonomi menengah ke bawah, sehingga cenderung lebih memilih langsung bekerja daripada melanjutkan pendidikan ke jenjang yang lebih tinggi. Oleh karena itu, diperlukan pelatihan yang dapat meningkatkan keterampilan praktis sesuai kebutuhan industri.Pelatihan difokuskan pada tiga aspek utama: penyusunan curriculum vitae (CV) profesional, strategi menghadapi wawancara kerja dalam bahasa Indonesia maupun bahasa Inggris, serta keterampilan digital melalui penggunaan Canva untuk pembuatan CV. Peserta terlibat secara aktif melalui sesi interaktif, simulasi, dan latihan kolaboratif. Hasil kegiatan menunjukkan adanya peningkatan kesadaran, kepercayaan diri, dan keterampilan peserta dalam mempersiapkan diri menghadapi dunia kerja. Kesimpulannya, integrasi literasi digital dan kemampuan bahasa Inggris dalam pelatihan berbasis masyarakat dapat meningkatkan daya saing lulusan SMA/SMK serta memberikan kontribusi nyata dalam mendukung kesiapan mereka menghadapi pasar kerja. Kata kunci: kemampuan bahasa Inggris, kesiapan kerja, keterampilan digital, pengabdian masyarakat, pendidikan vokasi